Perancangan Ulang Interior Mal Pelayanan Publik Kota Payakumbuh Dengan Pendekatan Perilaku (behavior) - Aulia Putri, Mayang; Cardiah, Tita; Retno Palupi, Fajarsani (eProceedings of Art & Design, 2024)
The purpose of establishing the Public Service Mall in Payakumbuh City is to facilitate the public in managing permits. Therefore, the interior of the public service office must be designed to be comfortable and user-friendly. This research employs a descriptive qualitative method, with primary data obtained through interviews, documentation, and observation, and secondary data derived from literature reviews and precedent studies. The findings of this study indicate that the design of the Public Service Mall requires a human-centered approach, specifically a behavioral approach that analyzes human activities within the space and creates a more organized and well-directed spatial layout. Additionally, clear directional signage is necessary for visitors. This redesign is expected to fulfill the primary objective of the Public Service Mall, which is to reduce queues and facilitate public service access. Keywords: Interior, public service mall, behavioral approach